Effect of Compensation, Work Discipline and Work Environment on Performance With Organizational Commitment As an intervening variable in PT. Cartenz Adventure Karanganyar - Gustiatun, Ambarwati (STIE AUB Surakarta)
The purpose of this study was to test the effect in compensation, discipline and work environment on the performance of the organization's commitment as an intervening variable in PT. Cartenz Adventure Karanganyar. The data of this study are primary data, obtained from a questionnaire or questionnaires. The analysis technique used is using validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. Hypothesis test results compensation is not significant effect on organizational commitment, job Discipline significant effect on organizational commitment, work environment significantly influence organizational commitment, Compensation significant effect on performance, working Discipline not significant effect on performance, workplace environment not significant effect on performance, organizational commitment significant effect on performance. Test results simultaneously (Test F) in the second equation is known the value of the significance F = 9.390 0.000 <0.05. It can be concluded jointly independent variables affect performance. Results of path analysis showed that: the direct effect on the performance of the variable compensation is greater than the indirect effect of compensation through the organization's commitment to Performance. Direct influence on the performance of work discipline variable is smaller than the indirect effect of labor discipline through the organization's commitment to Performance. Direct influence on the performance work environment variable is smaller than the indirect effect of the work environment through the organization's commitment to PerformanceKeywords: Compensation, Work Discipline, Work Environment, Organizational Commitment, Performance